PENGARUH PENERAPAN TIPE NUMBERED HEAD TOGETHER DALAM PEMBELAJARAN MATEMATIKA KELAS IV SD PONTIANAK UTARA - Oseriyola, Krispina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â  Abstract The purpose of this reasearch is to analyze effect of the applying type numbered head together approach to matter determines the LCM and HCF for learning outcomes of fourth grade in SDN 09 North Pontianak. Research methods that used is experimental method with Quasi Experimental Design, with Nonequivalent Control Group Design. Research population is all of fourth grade of two classes from class IVA to class IVB with total 58 students. The sample of this research are class IVA consist of 30 students (experiment) and class IVB consist of 28 students (control). The average learning outcomes of final test class IVA is 73,6 and class IVB is 64,64 gained tarithmetic (2,0148)>ttable Î±=5% (1,6736), then Ha acceptable. So, the conclution is there are two average significant differences learning outcomes of students, among students group that teach with apply methods of expository and students group that teach with apply of type numbered head together approach of fourth grade in SDN 09 North Pontianak. The value of effect size is 0,54 with are criteria, that is the type of numbered head together to give effect to the results of student learning in mathematics learning of fourth grade SDN 09 North Pontianak. Â  Keywords : Numbered Head Together, Learning Outcomes.